TINGKAT KEPENTINGAN ELEMEN ARSITEKTURAL PADA VIHARA VAJRA BUMI KERTAYUGA BERDASARKAN PERSEPSI UMAT BUDDHISME ALIRAN TRUE BUDDHA SCHOOL - Wijaya, Candra; Kalsum, Emilya; Caesariadi, Tri Wibowo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
Architecture reflects the evolving needs of humanity, including within the spiritual context. Religion and belief system play a crucial role in shaping religious architecture, which not only serves as a place of worship but also embodies symbolic values and religious practices. The diverse religious traditions in Indonesia create a rich religious landscape, including in the architecture of places of worship such as monasteries (vihara). This research focuses on Vajra Bumi Kertayuga Monastery in Pontianak, a physical representation of the teachings of the True Buddha School sect. The evaluation of its architectural elements aims to assess the alignment between the building